Taking action : creating sustainable change in student affairs - Ewell, Sara B.; Giblin, Joan; McNabb, Joe (Contemporary perspectives through action research across educational disciplines, 2023)
"Action Research can empower all administrators in higher education to engage more effectively in resolving challenges in colleges and universities. Scholar-practitioners are particularly well poised to impact three defined areas of practice: college students, faculty, and curriculum, teaching and learning. Through these three areas of foci broad issues within higher education are explored. Action Research is a powerful, localized methodology for impacting difficult and complex issues embedded in organizations. Higher education administrators regularly confront these types of difficult issues and hold the responsibility to solve these problems"--